Empowering Rural Parents to Support Youth Career Development: An Interim Report - Jeffery, Gary H.; Lehr, Ron; Hache, George; Campbell, Marjorie (Canadian Journal of Counselling and Psychotherapy, 1992)
Work being done on a three-year project aimed at developing innovative ways to help rural parents support the career development of 15-25-year-old youth is described. The project makes use of an innovative data-gathering strategy and innovative techniques for analyzing qualitative group interview data. The paper describes identified rural career-related needs and discusses proposed products designed to address these needs.